Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592

CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO